Answers

2014-04-21T15:11:36+05:30
The answerr is the option a .
0
The Brainliest Answer!
2014-04-21T15:34:42+05:30
The answer is option d)
see
( aq - bp ) ( br - cq )=abqr-acq²-b²pr+bpcq
then sum of roots for first equation
α+β=-b/a,αβ=c/a
and second is
α+ω=-q/p,αω=r/p
so
-b/a-β=-q/p-ω
ω=b/a-q/p+β
as
c/(aβ)=r/(pω)
ω=raβ/cp=b/a-q/p+β
therefore β=(b/a-q/p)/((ra/cp)-1)
 \beta = \frac{(pb-aq)}{ap} \frac{(ra-cp)}{cp}
and 
ω=(ra/cp)((b/a-q/p)/((ra/cp)-1))
=  \frac{ra}{cp} \frac{(pb-aq)}{ap} \frac{(ra-cp)}{cp}

1 5 1
vow so big thanks ur is correct nswer